Theoretical study of Semiconductor Laser dynamics - D. Al-Saeedi, Shakir; O. Oliewi, Mushtaq; Tuaimah , Ali Natheer; Emshary , C.A. (University of Thi-Qar Journal, 2019)
In the present work, we study the dynamics of semiconductor laser as the time behavior of the carriers and photons densities , the output power and finding the threshold injected current at steady state. Output intensity of the semiconductor laser under the effect of injection current modulation was studied too